The effect of 30 days of detraining on measures of Hbmass in ultra endurance triathletes - Eastwood, A.; Bourdon, P. C.; Snowden, K. R.; Gore, C. J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
It has recently been proposed that measures of haemoglobin mass (Hbmass) using the optimised CO rebreathing method1 may be used to detect illegal, autologous blood transfusions2,3, which are currently untraceable. If CO rebreathing method is to be introduced as an anti doping test, the stability or otherwise of Hbmass during periods of intensive training and detraining must be quantified. The purpose of this study was to determine the effect of a 30-day period of detraining on Hbmass in ultra endurance triathletes, since their training is extreme in the build up to a competition. Methods Ten recreational ultra endurance triathletes (range 29-44 years) participated in the study, after providing written consent to procedures approved by the AIS Ethics Committee. Measures of Hbmass were taken using the optimised CO rebreathing method1 10 days prior to an ultra endurance triathlon (3.8 km ocean swim, 180 km cycle, 42.2 km run) and after ~10, 20 and 30 days of detraining following the event. Typical error for Hbmass was 2.0% (90% CI = 1.5 - 3.4%). Maximum oxygen uptake (VO2max) was also assessed 10 days prior to the event and at the end of the 30-day detraining period, using the SASI metabolic cart4.Training volume from self-report diary decreased from ~20 hours per week in the 30 days prior to the event to <5 hours per week in the 30 day detraining period. Results There was a 2.7% (90% CI -4.7 to -0.7%) decrease in mean Hbmass from 863g to 840g in the 30-day detraining period, which was statistically significant (p=0.04). Mean VO2max decreased by 4.0% (90% CI -6.8 to -1.1%) from 4.86 L.min-1 to 4.67 L.min-1, which was also statistically significant (p=0.03). Body mass increased by 3.3% (90% CI 2.0 to 4.5%) from 75.6 to 78.0 kg, and there was a 29.8% (90% CI 23.0 to 37.0%) increase in skinfolds from 43.8 to 56.1 mm over the 30-day period. There was a weak non-significant correlation between the percent change in absolute Hbmass and the percent change in absolute VO2max (r=0.37, p= 0.28). Discussion A 30-day period of detraining caused a ~3% decrease in Hbmass in ultra endurance triathletes. This is a similar magnitude to that estimated by Garvican et al5 for a 20% decrease in 42 day training load in women cyclists, but not as large as the ~20% decrease seen after hospital bed rest for 4 weeks following a collision with a car6. If Hbmass is to be used for anti-doping purposes, any large reductions in training load, such as those associated with injury or illness must be considered when interpreting the results. However, changes of 3% are relatively small compared with the ~10% changes that might occur with autologous blood donation (e.g. 2 units of blood ~ 100g of Hbmass) or extensive use of recombinant EPO.